Combined Precursor Engineering and Grain Anchoring Leading to MA‐Free, Phase‐Pure, and Stable α‐Formamidinium Lead Iodide Perovskites for Efficient Solar Cells. Issue 52 (18th November 2021) - Ling, Xufeng; Zhu, Hongwei; Xu, Weidong; Liu, Cheng; Pan, Linfeng; Ren, Dan; Yuan, Jianyu; Larson, Bryon W.; Grätzel, Carole; Kirmani, Ahmad R.; Ouellette, Olivier; Krishna, Anurag; et al.
Abstract: α‐Formamidinium lead iodide (α‐FAPbI3 ) is one of the most promising candidate materials for high‐efficiency and thermally stable perovskite solar cells (PSCs) owing to its outstanding optoelectrical properties and high thermal stability. However, achieving a stable form of α‐FAPbI3 where both the composition and the phase are pure is very challenging. Herein, we report on a combined strategy of precursor engineering and grain anchoring to successfully prepare methylammonium (MA)‐free and phase‐pure stable α‐FAPbI3 films. The incorporation of volatile FA‐based additives in the precursor solutions completely suppresses the formation of non‐perovskite δ‐FAPbI3 during film crystallization. Grains of the desired α‐phase are anchored together and stabilized when 4‐ tert ‐butylbenzylammonium iodide is permeated into the α‐FAPbI3 film interior via grain boundaries. This cooperative scheme leads to a significantly increased efficiency close to 21 % for FAPbI3 perovskite solar cells. Moreover, the stabilized PSCs exhibit improved thermal stability and maintained ≈90 % of their initial efficiency after storage at 50 °C for over 1600 hours. Abstract : Formamidinium (FA)‐based additives in precursor solutions suppressed the formation of the undesired δ phase during the crystallization of FAPbI3 perovskites, and heat‐induced permeation of 4‐ tert ‐butylbenzylammonium iodide (tBBAI) into inner perovskite grains stabilized the α structure. Solar cells assembled from this material exhibited improved power conversion efficiency and stability.